On-line mixing and emission characteristics of diesel engine with DME injected into fuel pipeline - Lao, Liyun (VINČA Institute of Nuclear Sciences, 2016)
This article presents a new on-line dimethyl ether (DME)/diesel mixing method, researches its blend characteristics, and also validates combustion and emission effects on a light-duty direct injection engine. This new blend concept is that DME is injected into the fuel pipeline to mix with local diesel as the injector stops injection, and this mixing method has some advantages, such as utilization of the original fuel system to mix DME with diesel intensively, flexibility on adjustable mixing ratio varying with the engine operating condition, and so on. A device was designed to separate DME from the blends, and its mixing ratios and injection quantity per cycle were also measured on a fuel pump bench. The results show that compared with the injected diesel, the percentages of DME injected into fuel pipeline are 13.04%, 9.74%, 8.55% and 7.82% by mass as the fuel pump speeds increase, while DME injected into fuel pipeline are 45.46%, 35.53%, 31.45% and 28.29% of wasting DME. The power outputs of engine fuelled with the blends are slight higher than those of neat diesel at low speeds, while at high speeds, its power outputs are a little lower. Smoke emissions of the blends are lower about 30% than that of neat diesel fuel at medium and high loads with hardly any penalty on smoke and nitrogen oxides (NOx) emissions at light loads. NOx and hydrocarbons (HC) emissions of the blends are slight lower than that of neat diesel fuel at all loads.
Keywords: Diesel engine; Dimethyl ether (DME); Fuel pipeline; Mixing; Emission characteristics